Snow, Silence, and Story: Narrative Metacognition in Sami Student Learning in Arctic Norway - Maria Nilsen; Thomas Haug; Emma Lersen (Journal Emerging Technologies in Education, 2025)
Background. In Arctic Norway, the education of Indigenous Sami students involves navigating linguistic, cultural, and ecological dimensions that differ markedly from mainstream schooling norms. Traditional pedagogies often overlook how local knowledge systems and environmental contexts shape learning processes. Purpose.  This study investigates how narrative metacognition-learners’ awareness and regulation of their thought processes through storytelling-emerges among Sami students in Arctic educational settings. The research aims to explore how narrative practices, silence, and spatial awareness function as cognitive tools within Sami learners’ reflective processes. Method. A qualitative research design was employed, using narrative inquiry and ethnographic observation in two Sami-majority schools. Data were collected through student storytelling sessions, classroom reflections, and teacher interviews. Results. The findings reveal that Sami students frequently engage in self-reflective meaning-making through oral narratives and strategic use of silence, often linked to landscape, seasonal rhythms, and intergenerational knowledge. These metacognitive expressions reflect a culturally embedded logic of learning that resists conventional Eurocentric measures of participation and articulation. Conclusion. The study concludes that recognizing and supporting narrative metacognition can enhance culturally responsive pedagogy in Indigenous education contexts. These insights contribute to both Indigenous education research and broader efforts to decolonize learning environments.